Animal History in the Modern City Exploring Liminality - Wischermann, Clemens; Steinbrecher, Aline (Bloomsbury Academic, 2018)
Assembling an impressive cast of contributors, this volume employs liminality as a lens through which to study the social and cultural history of animals in the modern city. It includes a variety of case studies, such as the horse-human relationship in the towns of New Spain, hunting practices in 17th-century France, the birth of the zoo in Germany and the role of the stray dog in the Victorian city, demonstrating the interrelated nature of animal and human histories. This is a vital resource for scholars and students interested in animal studies, urban history and historical geography.